2020
DOI: 10.1101/2020.10.14.340083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From amazing work to I beg to differ - analysis of bioRxiv preprints that received one public comment till September 2019

Abstract: While early commenting on studies is seen as one of the advantages of preprints, the nature of such comments, and the people who post them, have not been systematically explored. We analysed comments posted between 21 May 2015 and 9 September 2019 for 1,983 bioRxiv preprints that received only one comment. Sixty-nine percent of comments were posted by non-authors (n=1,366), and 31% by preprint authors (n=617). Twelve percent of non-author comments (n=168) were full review reports traditionally found during jou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In addition to Twitter, the comments section of preprint servers can be used as a public forum for discussion and review. However, an analysis of all bioRxiv comments from September 2019 found a very limited number of peer-review style comments [ 43 ]. Despite increased publicity for established preprint review services (such as PREreview [ 44 , 45 ]), there has been a limited use of these platforms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Twitter, the comments section of preprint servers can be used as a public forum for discussion and review. However, an analysis of all bioRxiv comments from September 2019 found a very limited number of peer-review style comments [ 43 ]. Despite increased publicity for established preprint review services (such as PREreview [ 44 , 45 ]), there has been a limited use of these platforms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Twitter, the comments section of preprint servers can be used as a public forum for discussion and review. However, an analysis of all bioRxiv comments to September 2019 found a very limited number of peer-review style comments [43]. Despite increased publicity for established preprint-review services (such as PREreview [44,45]), there has been limited use of these platforms [46].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are lower than in a recent survey of authors from Latin America (SCIELO) where preliminary results of a survey indicate there were around 40% of authors who posted a preprint and they mostly feel posting a preprint is something beneficial (29). In a recent analysis of comments of 1,983 bioRxiv preprints (before the COVID pandemic) Malicki et al (30) found that 12% (N=168) of comments were full peer review reports. and hypothesised beneficial effects of the comments for the authors and the scientific community.…”
Section: Discussionmentioning
confidence: 99%